Numerical Simulation of Gas Ventilation Mode in Highway Gas Tunnel. (17th February 2021) - Zhang, Jihua; Dong, Yun; Chen, Yadong; Sun, Huasheng; Wu, Jingke; Liu, Weili; Chen, Jiarui; Pan, Shiqiang
Abstract : When the mountain tunnel projects passing through the complex formation with coal, it happened along with disaster accidents such as gas outburst, gas combustion, and gas explosion. These disasters should seriously threaten the safety and life of the construction personnel and affect the normal operation of the tunnel construction. Ventilation is the most effective means to control gas, fire, dust, heat, and other disasters. To study the effects of different ventilation modes in highway gas tunnels, Fluent software was used to simulate forced ventilation, exhaust ventilation, and mixed ventilation in a high gas tunnel of a highway in Hunan. The distribution law of the airflow velocity and gas concentration of these three ventilation modes were obtained to determine the optimal ventilation system. It was shown that vortex zones of different ranges formed in the tunnel for all three ventilation modes, and the gas concentration was higher in the vortex zone than in other regions. Mixed ventilation of them is superior to the other two modes, showing the best ventilation effect with regard to airflow velocity and gas concentration.